Using prototypical sites to model methane emissions in Colorado’s Denver-Julesburg basin using mechanistic emissions estimation tool - Mollel, Winrose A., author; Olsen, Daniel B., advisor; Zimmerle, Dan, advisor; Baker, Dan, committee member; Quinn, Jason, committee member (Colorado State University. Libraries, 2023)
The BU methods estimate emissions by considering activity factors and emission factors averages for an extended period for a large area. Some TD methods use the ethane-methane ratio to attribute methane emissions from oil and gas facilities. The bottom-up (BU) inventory estimates are often used to drive the attribution of emissions indicated by TD data to different emission source categories. Despite widespread use, recent studies indicate that traditional bottom-up (BU) inventory methods do not adequately capture how variations in throughput and failure conditions impact gas composition and rate of emissions. Traditional BU methods typically do not model gas composition, although it differs among different facility configurations and impacts emissions from different equipment within one facility. Since most BU inventories utilize fixed emissions factors, emissions also do not scale due to throughput, which is particularly important for large emitters associated with failure conditions. Mechanistic emissions modeling can be used to address these shortcomings and make BU modeling more effective. This study illustrates how mechanistic modeling highlight changes in emissions due to variable throughput and equipment pressures and temperatures for the same production routed through the same or different production facility designs. The study uses the same mechanistic models to illustrate how the frequency of failure modes impacts both gas composition and total emissions. Results indicate mechanistic modeling could explain observed gas composition shifts in emitted emissions from production and midstream facilities over time, a key modeling input to improve voluntary and regulatory methane mitigation efforts.
Keywords: DJ basin; methane emissions; top down (TD); MAES; bottom up (BU); natural gas